Caracterização do polietileno de ultra alta massa molar processado por moagem de alta energia - Mendes, Luciana Biagini (2010)
This research was an exploratory study of the changes that high energy mechanical milling can induce in ultra high molecular weight polyethylene (UHMWPE), using the mills Spex, Attritor and Planetary, and several times and reasons for grinding. The milling products were characterized using scanning electron microscopy (SEM), optical microscopy (OM), differential scanning calorimeter (DSC), x-ray diffraction (XRD), x-ray fluorescence (XRF), and intrinsic viscosity for calculate the viscosity average molecular weight. For the analysis of micrographs observed the morphological change of particles with the grinding, the particles are initially rounded and the milling time increases the aspect ratio, acquire the form of flakes. Changing the shape in Spex mill occurs in less time, because it is a mill more energetic that Attritor and Planetary. By analysis of DSC was possible to observe the influence of high energy mechanical milling on melting and crystallization temperatures, and the percentage of crystalline phase of UHMWPE. Was used deconvolution of peaks in xray diffraction patterns for better identification of the peaks of monoclinic and orthorhombic crystalline structures. Observed the formation of monoclinic phase in the UHMWPE processed in high energy mills, to a greater percentage in the mill Attritor, possibly because it has a temperature control and avoiding a reversal of the monoclinic crystalline structure in orthorhombic crystalline structure.